Mathematics for elementary teachers : - Bennett, Albert B (McGraw-Hill, 2004)
This book provides inductive activities for prospective elementary school teachers and incorporates the use of physical models, manipulatives, and visual images to develop concepts and encourage higher level thinking. (This text contains activity sets, one corresponding to each section of the companion text, Mathematics for Elementary Teachers: A Conceptual Approach